Reversal Modes in Asymmetric Ni Nanowires - Escrig-Murua, J; Pereira-Abarca, A (2012)
We have investigated the evolution of the magnetization reversal mechanism in asymmetric Ni nanowires as a function of their geometry. Circular nanowires are found to reverse their magnetization by the propagation of a vortex domain wall, while in very asymmetric nanowires the reversal is driven by the propagation of a transverse domain wall. The effect of shape asymmetry of the wire on coercivity and remanence is also studied. Angular dependence of the remanence and coercivity is also addressed. Tailoring the magnetization reversal mechanism in asymmetric nanowires can be useful for magnetic logic and race-track memory, both of which are based on the displacement of magnetic domain walls. Finally, an alternative method to detect the presence of magnetic drops is proposed. © 2012 Elsevier B.V.